147k views
0 votes
Solve! if you can!
And give correct answers showing proper steps...​

Solve! if you can! And give correct answers showing proper steps...​-example-1
User FireZenk
by
5.4k points

1 Answer

4 votes

Answer:


x = 1(5)/(12)

Explanation:


(5x)/(3) - (x - 2)/(4) = 2 (1)/(4) - (x - (2x - 1)/(3) ) \\ (5x)/(3) - (x - 2)/(4) = (9)/(4) - x + (2x - 1)/(3) \\ (20x)/(12) - (3x - 6)/(12) = (9)/(4) - x + (2x - 1)/(3) \\ (17x + 6)/(12) = (9 - x)/(4) + (2x - 1)/(3) \\ (17x + 6)/(12) = (27 - 3x)/(12) + (8x - 4)/(12) \\ (17x + 6)/(12) = (23 + 5x)/(12) \\ 12(17x+ 6) = 12(23 + 5x) \\ 17x + 6 = 23 + 5x \\ 17x - 5x = 23 - 6 \\ 12x = 17 \\ x = (17)/(12) \\ x = 1 (5)/(12) \\

User Alex Sasnouskikh
by
5.9k points